NIOSOMES: CLASSIFICATION, PREPARATION AND APPLICATION - Kamlesh Maurya; Arpita Singh; Swarnima Pandey; Nitish Kumar; Mohd. Aqil Siddhiqui (International Journal of Indigenous Herbs and Drugs, 2021)
Vesicular medication delivery system, for instance, niosomes may be a novel medication delivery system, during which the answer is enclosed in vesicle which is formed by Non-ionic surfactant. Structurally, niosomes are almost like liposomes, therein they’re also made from a bilayer. However, the bilayer within the case of niosomes is formed from non-ionic surface actives agents instead of phospholipids as seen just in case of liposomes. Niosomes tackled the difficulty of insolubility, instability, low bioavailability and fast debasement of medicines. The vesicular system of niosomes, with their bilayer structure assembled by nonionic surfactants, is in a position to reinforce the bioavailability of a drug to a predetermined area for a period. The both hydrophilic or lipophilic nature (amphiphilic nature) of niosomes increase their capacity in encapsulating lipophilic or hydrophilic drugs. Differents type additives, such as cholesterol, are often wont to maintain the rigidity of the niosomes structure. The basic aspects of niosomes, such as their structural components, methods of preparation, and current applications to various diseases.